Establishment of the All-day School in Lithuania: An Institutional Analysis - Dilytė, Asta; Skučienė, Daiva; Dunajevas, Eugenijus (Acta Paedagogica Vilnensia, 2020)
The traditional model of general education organization, which focuses only on the provision of human capital as a guarantor of welfare, cannot effectively achieve this goal without removing other barriers to the child’s development (OECD 2016). The acquisition of human capital also significantly depends on a person’s social and cultural capital. In addition to its traditional functions, a school can also provide social and cultural capital by providing a space for the interaction of various social networks, promotion of new ideas and cultural diversity, and the involvement of social partners in school activities (Healy 2001). An all-day school is one of the tools to provide children with social and cultural capital. Despite the existing disparities between a pupil’s achievement and the low level of their social and cultural capital (Shleider 2018), all-day schools are not widespread.According to John Elster (2000), the actions of an organization are determined firstly by opportunities and then by interests. Opportunities are determined by economic, institutional, and psychological constraints. The aim of this study is to analyze the institutional limitations of establishing an all-day school. Elinor Ostrom (2009) argues that the whole set of institutions that determine the situation of action (in our case, the establishment or non-establishment of an all-day school) can be divided into 7 groups: boundaries, positions, choices, aggregation, information, potential outcomes, and payoff institutions. The institutional limitations of all-day school establishment were analyzed in the study using a qualitative content analysis of documents on the principle of axial coding, distinguishing subcategories and categories. The results of the study showed that institutional constraints do not limit access to an all-day school, but there is a high concentration of power, lack of accountability for service quality, and parental costs that may limit access to services for children from lower-income families with the greatest social and economic disadvantages.
Keywords: all day school; institutions; educational; social capital; cultural capital